Peningkatan Pengetahuan Melalui Pendidikan Tentang Protokol Kesehatan di Era New Normal di SDN Emaus Wonosari Kediri - Wahyuningsih, Aries; Fitria, Indraningrum; Kurnia, Erlin (Jurnal Abdimas Jatibara, 2022)
The Covid-19 pandemic has affected condition of society and also impact to global society. The government has implemented the adaptation of the New Lifestyle. The main principle of the new normal is to get used to living with a new lifestyle by requiring people to continue to apply health protocols. Adherence to health protocols such as washing hands with soap and running water or hand sanitizer, wearing masks, maintaining distance, limiting mobilization away from crowds and avoiding eating together. Objectives to provide appropriate health education about health protocols in the new normal era for children at Emaus Elementary School of Wonosari Kediri. The approach method used was community-based education, the subjects used are elementary school students using posters and demonstrations about health protocols with 6M to support clean and healthy living behavior in limited face-to-face learning. The results of the implementation of PkM activities are that all students (100%) have received health educations, students are able to demonstrate how to wash hands properly and use masks correctly. Able to answer questions about social distancing and maintaining health by vaccination. The implementation of community service is obtained through health counseling, students at Emaus Elementary School have awareness about the 6M health protocol and apply it during at school.